Handgrip strength of community-dwelling elderly in Nakhon Ratchasima Province, Thailand - Horpibulsuk, Jitwadee; Nutkhum, Wannisa; Jongjol, Pornsiri (Biomedical Sciences and Clinical Medicine, 2019)
Objective To investigate handgrip strength (HGS) in Thai elderly living in Nakhon Ratchasima Province, Thailand, and to examine factors related to HGS. Methods In this is a cross-sectional analytical study, participants were elderly individuals (age >60 years) living in Nakhon Ratchasima, Thailand. Demographic characteristics, anthropometric measurements, and Barthel Activities of Daily Living index (ADL) were recorded. Assessment of grip strength of the dominant hand was conducted following standardized testing procedures of the American Society of Hand Therapists. Results The mean age (±SD) of the 491 participants was 69.15±6.86 years. The mean HGS for male participants was significantly higher than for females (24.93±7.45 vs 16.17±4.82, p<0.001), but there was a significant decline in HGS with age in both genders (r=-0.310, p<0.01). Dividing participants by BMI found that normal and overweight individuals had a higher HGS than underweight participants (p<0.001). Conclusion As age increases, the HGS of both males and females declines. Elderly males have a higher HGS than females. Elderly (age ≥ 60 years) of both genders have a statistically significantly higher HGS than underweight individuals.